Ultra-widefield retinal imaging: an update on recent advances - Patel, Samir N. (Ther Adv Ophthalmol, 2020)
The development of ultra-widefield retinal imaging has accelerated our understanding of common retinal diseases. As we continue to validate the diagnostic and prognostic significance of pathology in the retinal periphery, the ability to visualize and evaluate these features in an efficient and patient-friendly manner will become more important. Current interest in ultra-widefield imaging includes the development of potential biomarkers of disease progression and indicators of preclinical disease development. This article reviews the current ultra-widefield imaging systems and recent advances in their applications to clinical practice with a focus on diabetic retinopathy, retinal vein occlusion, uveitis, and pediatric retina.